2023
DOI: 10.3928/1081597x-20230207-02
|View full text |Cite
|
Sign up to set email alerts
|

The Non-uniform Distribution of Horizontal and Vertical Crystalline Lens Rise Using Optical Coherence Tomography

Abstract: Purpose: To observe the crystalline lens rise (CLR) in horizontal and vertical orientations using anterior segment optical coherence tomography (AS-OCT). Methods: Non-invasive swept-source AS-OCT was used to measure the lens thickness, CLR, and angle-to-angle distance (ATA) in both the horizontal and vertical orientations. Anterior chamber depth (ACD) and horizontal white-to-white corneal diameter were obtained using the Pentacam HR (Ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The study showed that ICL diameter and ACD were the most influential factors, a relatively larger ICL diameter and a greater preoperative ACD directly result in higher postoperative vault. In addition, CLR, refers to the anterior movement of the natural crystalline lens within the eye, is also an important factor in ICL surgery ( 31 ). CRL can affect the position and movement of the natural lens and the ICL, excessive CLR can lead to potential complications such as contact between the ICL and the natural lens, which may result in elevated IOP.…”
Section: Excessive Icl Vaultmentioning
confidence: 99%
“…The study showed that ICL diameter and ACD were the most influential factors, a relatively larger ICL diameter and a greater preoperative ACD directly result in higher postoperative vault. In addition, CLR, refers to the anterior movement of the natural crystalline lens within the eye, is also an important factor in ICL surgery ( 31 ). CRL can affect the position and movement of the natural lens and the ICL, excessive CLR can lead to potential complications such as contact between the ICL and the natural lens, which may result in elevated IOP.…”
Section: Excessive Icl Vaultmentioning
confidence: 99%